2015
DOI: 10.1177/1748895815599580
|View full text |Cite
|
Sign up to set email alerts
|

‘I wannabe a copper’: The engagement of Police Community Support Officers with the dominant police occupational culture

Abstract: Drawing upon ethnographic research with PCSOs working in two neighbourhood policing teams in Northern England, this article presents a typology of PCSO orientations to work and for the first time details the ways in which PCSOs utilise aspects of the dominant culture to manage the discord between aspirations and opportunities within the PCSO role. Engagement with aspects of the dominant culture varied according to career aspirations and orientations to work; 'Frustrated PCSOs' were most likely to endorse cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…These tendencies towards cultural negativity in organizational discourses in respect of volunteer police officers perhaps reflect a collision between the concept of volunteer officers, on the one hand, and of a ‘Regular-centric’ (Britton and Callender, 2017) dominant cultural typology of what it means to be a police officer, on the other hand (Cosgrove, 2016). Despite a prominent international drive for pluralization of policing that places greater emphasis and importance on volunteers, significant fractures remain within the extended policing family that suggest the need for significant further cultural attention.…”
Section: Discussionmentioning
confidence: 99%
“…These tendencies towards cultural negativity in organizational discourses in respect of volunteer police officers perhaps reflect a collision between the concept of volunteer officers, on the one hand, and of a ‘Regular-centric’ (Britton and Callender, 2017) dominant cultural typology of what it means to be a police officer, on the other hand (Cosgrove, 2016). Despite a prominent international drive for pluralization of policing that places greater emphasis and importance on volunteers, significant fractures remain within the extended policing family that suggest the need for significant further cultural attention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence suggested that when the PCSO role was first introduced it was not well integrated into the 'police extended family' (Johnston, 2005), and police officers were often confused about the nature of the role due to lack of guidelines (Paskell, 2007). Future research on how the relationship between police officers and trainee PCSOs may impact the learning journey will help shed light on the topic (Cosgrove, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Data from a sample of newly recruited Police Community Support Officers (PCSOs) were collected in 2009/10. The role of the PCSO was introduced with the enactment of the Police Reform Act in 2002 (Cosgrove, 2016), which created the possibility for police support staff, endowed with limited powers, to undertake a variety of uniformed patrolling tasks. Defined as "uniformed civilian employees of [a] police authority .…”
Section: The Training Of Police Community Support Officers and The Lementioning
confidence: 99%
“…Thirdly, well-established characteristics of police culture resonate with normalising dirty work. Westley's (1970) work identified aspects of police occupational culture -in-group solidarity, preoccupation with danger, isolation from the public, sexism and racism, willingness to use force, relations with minority groups, discretion in decision-making -which others (Skolnick, 1966(Skolnick, , 2008Silvestri, 2003;Reiner, 2010;Loftus, 2010;Cockcroft, 2013;Cosgrove, 2016;Loftus et al, 2016) have explored as dimensions of police cultures. As discussed later, cultures within increasingly diverse police organisations can be both forces for good -a dimension of coping with hostility, and badreproducing inequality and isolation.…”
Section: The Dirty Work Of Policingmentioning
confidence: 99%